2014
DOI: 10.1590/so100-720320140005128
|View full text |Cite
|
Sign up to set email alerts
|

Fatores ambientais e endometriose: um ponto de vista

Abstract: Endometriose é uma afecção ginecológica comum, que atinge de 10 a 15% das mulheres no período reprodutivo e até metade das mulheres com dor pélvica crônica e/ou infertilidade 1,2 . Estima-se que o número de mulheres com endometriose seja de 7 milhões nos Estados Unidos da América e de mais de 70 milhões no mundo. Em países industrializados, essa é uma das principais causas de hospitalização ginecológica 3 . Apesar de ser uma das doenças mais estudadas em ginecologia 4 , alguns aspectos continuam sendo alvo de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…Endometriosis is a gynecological disorder affecting the wellbeing of 5%-15% of women of reproductive age, with a prevalence of 5%-50% in infertile women and 32% in women with chronic pelvic pain (Bellelis et al ., 2014). Studies showed that 30% to 50% of the women with endometriosis are infertile (Zhang et al ., 2014; Zhu et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endometriosis is a gynecological disorder affecting the wellbeing of 5%-15% of women of reproductive age, with a prevalence of 5%-50% in infertile women and 32% in women with chronic pelvic pain (Bellelis et al ., 2014). Studies showed that 30% to 50% of the women with endometriosis are infertile (Zhang et al ., 2014; Zhu et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…reviewed the direct medical and nonmedical burden associated with endometriosis. The authors suggested that endometriosis places a considerable burden on patients and society (Bellelis et al ., 2014; Gao et al ., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Endometriosis is characterized by implantation and growth of endometrial tissue outside the uterine cavity (Agarwal et al 2005). It is often associated with clinical symptoms that impair quality of life, including dysmenorrhoea, dyspareunia, acyclic pelvic pain, infertility and alterations of intestinal and urinary habits (Kyama et al 2003, Bellelis et al 2014, Vercellini et al 2014. Endometriosis lesions can form at different sites within the pelvis such as superficial peritoneal lesions, ovarian endometriomas (cysts) and may also be detected as deep-infiltrating lesions that can compromise other organs such as rectum and bladder (Chapron et al 2006).…”
Section: Introduction Prevalence Characteristics and Socioeconomic Imentioning
confidence: 99%
“…Prevalence is up to 20% in women of reproductive age and 30 to 50% in infertile women, representing one of the most common gynecological diseases, with rare cases before menarche. It is estimated that more than 70 million women in the world are affected by endometriosis (Bellelis et al, 2010;Bellelis et al, 2014;Bianco et al, 2011;Nácul and Spritzer, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The loss of sensitivity of the endometrium to progesterone during the menstrual cycle is another recognized causative factor of endometriosis. As progesterone levels decrease in the secretory phase, the cytokines, proinflammatory chemokines and matrix metalloproteinase (MMPs) levels increase, in order to prepare the endometrium tissue for the intense inflammatory process caused by menstruation (Bellelis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%